What Are Public Services Worth, and to Whom? Non-parametric Estimation of Capitalization in Pune - Lall, Somik V.; Lundberg, Mattias (2012)
The availability and quality of basic public services are important determinants of urban quality of life. In many cities, rapid population growth and fiscal constraints are limiting the extent to which urban governments can keep up with increasing demand for these services. It therefore becomes important to prioritize provision of those services to best reflect local demand. We present a strategy to estimate the demand for public services, which is sensitive to heterogeneity in preferences across types of households, and the non-parametric estimation addresses problems arising from functional form restrictions. Using data from Pune, India, we estimate the demand for public services, as represented by the marginal change in the self-assessed monthly rental price of dwellings from the services. We find that the value of publicly-provided services accruing to the poor is greater than that going to wealthier households, and even untargeted across-the-board investment in specific services can be progressive.